2010
DOI: 10.1039/b917256d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structures of lanthanide 4-benzyloxy benzoates: Influence of electron-withdrawing and electron-donating groups on luminescent properties

Abstract: Three new 4-benzyloxy benzoic acid derivatives [4-benzyloxy benzoic acid = HL1; 3-methoxy-4-benzyloxy benzoic acid = HL2; 3-nitro-4-benzyloxy benzoic acid = HL3] have been employed as ligands for the support of six lanthanide coordination compounds [Tb 3+ = 1-3; Eu 3+ = 4-6] with the aim of testing the influence of electron releasing (-OMe) or electron withdrawing (-NO 2 ) substituents on the photophysical properties. The new complexes have been characterized by a variety of spectroscopic techniques and two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 58 publications
0
59
0
Order By: Relevance
“…However, the overall quantum yields and the sensitization efficiency noted for both the lanthanide compounds in the current study are found to be somewhat inferior as compared with various lanthanide benzoate complexes reported earlier in our laboratory. [3][4][5] The fact that both the lanthanide complexes derived from 4-[4-(9H-carbazol-9-yl)butoxy]benzoate (1 and 3) exhibit residual ligand emission in the 375-475 nm region, as can be noted from the respective emission spectra (Fig. 6 and 8), indicates the modest efficiency of energy transfer from the ligand to the Ln 3+ center.…”
Section: Quantum Yields and Sensitisation Efficiencymentioning
confidence: 95%
See 3 more Smart Citations
“…However, the overall quantum yields and the sensitization efficiency noted for both the lanthanide compounds in the current study are found to be somewhat inferior as compared with various lanthanide benzoate complexes reported earlier in our laboratory. [3][4][5] The fact that both the lanthanide complexes derived from 4-[4-(9H-carbazol-9-yl)butoxy]benzoate (1 and 3) exhibit residual ligand emission in the 375-475 nm region, as can be noted from the respective emission spectra (Fig. 6 and 8), indicates the modest efficiency of energy transfer from the ligand to the Ln 3+ center.…”
Section: Quantum Yields and Sensitisation Efficiencymentioning
confidence: 95%
“…Eu(L) 3 (tmphen) (5). Elemental analysis (%): calcd for C 85 H 76 EuN 5 O 9 (1463.48): C, 69.76;H, 5.23;N, 4.79;found C, 69.81;H, 5.28;N, 4.83.…”
Section: 10mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the five emission bands, the electric dipole transition 5 D0→ 7 F2 around 616 nm is the strongest. In addition, the ratio of electric dipole transition and magnetic dipole transition ( 5 D0→ 7 F1) of Complexes 1 and 2 are 3.31 and 4.28, respectively, which indicates that the coordination environment of Eu 3+ complexes are not center symmetric [50][51][52][53][54]. The luminescence intensities of electric dipole transition of Complexes 1 and 2 are 0.74 × 10 5 and 1.4 × 10 5 , respectively.…”
Section: Luminescence Of the Europium Complexesmentioning
confidence: 83%